Social entrepreneurship and enterprises in economic and social development - Ramos, Blanca; Lawson, Katharine Briar-; Miesing, Paul (New York : Oxford University Press, 2021)
'This book shows how social entrepreneurship and social enterprises can integrate social and economic development. These dual mission ventures striving to achieve both financial sustainability and social good are especially pathbreaking approaches in reducing economic, education, health, technology, and other disparities among marginalized individuals, families, and communities. While this global movement varies in pace and scope, we feature snapshots from eight countries or regions. This volume focuses especially on emerging economies and those in transition, featuring African countries of Kenya and Tanzania, Albania, Argentina, Central Asian countries of Kyrgyzstan and Tajikistan, Cuba, India, Russian Federation, and Taiwan. We examine a variety of ventures and their social policy context as they attempt to meet human needs while simultaneously also attaining financial sustainability'--
Includes bibliographical references and index.
Buku Bacaan Asas Fakulti Ekonomi dan Pengurusan.
Keywords: Social entrepreneurship -- Developing countries; Entrepreneurship -- Social aspects -- Developing countries; Developing countries -- Social policy; Economic development -- Developing countries